Prophylactic inguinal lymphadenectomy for high-risk cN0 penile cancer: The optimal surgical timing - Ma, Shanjin; Zhao, Jian; Liu, Zhiwei; Wu, Tao; Wang, Sheng; Wu, Chengwen; Pan, Lei; Jiang, Xiaoye; Guan, Zhihao; Wang, Yanjun; Jiao, Dian; Yan, Fengqi; et al. (Frontiers in Oncology, 2023)
Background: Few reports have investigated the oncologically safe timing of prophylactic inguinal lymphadenectomy for penile cancer patients with clinically normal inguinal lymph nodes (cN0), particularly those who received delayed surgical treatment. Methods: The study included pT1aG2, pT1b-3G1-3 cN0M0 patients with penile cancer who received prophylactic bilateral inguinal lymph nodes dissection (ILND) at the Department of Urology of Tangdu Hospital between October 2002 and August 2019. Patients who received simultaneous resection of primary tumor and inguinal lymph nodes were assigned to the immediate group, while the rest were assigned to the delayed group. The optimal timing of lymphadenectomy was determined based on the time-dependent ROC curves. The disease-specific survival (DSS) was estimated based on the Kaplan–Meier curve. Cox regression analysis was used to evaluate the associations between DSS and the timing of lymphadenectomy and tumor characteristics. The analyses were repeated after stabilized inverse probability of treatment weighting adjustment. Results: A total of 87 patients were enrolled in the study, 35 of them in the immediate group and 52 in the delayed group. The median (range) interval time between primary tumor resection and ILND In of the delayed group was 85 (29-225) days. Multivariable Cox analysis demonstrated that immediate lymphadenectomy was associated with a significant survival benefit (HR, 0.11; 95% CI, 0.02–0.57; p = 0.009). An index of 3.5 months was determined as the optimal cut-point for dichotomization in the delayed group. In high-risk patients who received delayed surgical treatment, prophylactic inguinal lymphadenectomy within 3.5 months was associated with a significantly better DSS compared to dissection after 3.5months (77.8% and 0%, respectively; log-rank p＜0.001). Conclusions: Immediate and prophylactic inguinal lymphadenectomy in high-risk cN0 patients (pT1bG3 and all higher stage tumours) with penile cancer improves survival. For those patients at high risk who received delayed surgical treatment for any reason, within 3.5 months after resection of the primary tumor seems to be an oncologically safe window for prophylactic inguinal lymphadenectomy.